A review on future planar transmission line. Issue 1 (31st December 2016) - Kumar, Ashok; Saini, Garima; Singh, Shailendra
Abstract: Substrate Integrated Waveguide (SIW) is an emerging trend in planar technology. The SIW structure consists of two rows of conducting cylinders in a dielectric substrate. The average power-handling capacity of an SIW structure is primarily determined by its substrate materials and its geometric topology. The power-handling capability depends on the nature of SIW circuits. Microwave and millimeter wave components can be integrated on SIW. It acts as a bridge between planar and non-planar technology. By using innovative fabrication techniques, SIW technology combines the classical planar circuits and metallic waveguide. The animus of the study is to provide the idea on design and fabrication of SIW structures and comparison between different topologies used for size reduction and dominant mode bandwidth enhancement.